Energy Conversion Efficiency Enhancement of a Normal Wind Turbine Combining a Fuzzy Control Method and Mechanical Centrifugal Modules - Xunwei Tong; Yuchen Sun; Xu Zhang; Zheng Li; Liwei Ren (IEEE Access)
Currently, low-wind speed shutdown and medium-wind speed inefficiency are the main problems plaguing wind turbines. This paper presents a wind turbine with a real-time adaptive regulation (RAR) system. It includes a sensor subsystem, a variable structure generator, and mechanical centrifugal modules. The above components collaborate for adaptive control of the wind turbine. The sensor subsystem is used to obtain the wind speed and generator speed in real time. Using a fuzzy control method, the optimal number of accessed coils in the variable structure generator can be determined. The mechanical centrifugal modules realize the regulation process through centrifugal force. Theoretical analysis and simulation of the energy conversion efficiency are executed. A physical prototype is machined. Performance experiments are conducted on the prototype. The results show that the RAR system expanded the operating range of wind turbine by 32%. It also improved the energy conversion efficiency by up to 36%. Compared with normal wind turbines, the RAR wind turbine solves the problems of low-wind speed shutdown and medium-wind speed inefficiency. The combination of a fuzzy control method and mechanical centrifugal modules proposed in this paper provides an effective solution for improving energy utilization in large-scale wind farms.